Pengaruh Profitabilitas, Lingkungan Kerja, dan Gaji Terhadap Loyalitas Karyawan (Studi Kasus pada PT MBKV Cabang Cianjur Utara dan Sukabumi Utara) - Elita Melani, Rini Syahril Fauziah (Nusa Putra University, 2020)
Employee loyalty in a company is a valuable part of the company's assets, because loyal employees can uphold company values. So that the opportunity to increase company profits is even greater. Employee loyalty (HR) is also often referred to as the key to the development of a company. Especially if it is supported by adequate company facilities, of course it will increase employee performance and loyalty to the company. This research paper aims to determine what is a significant influence on employee loyalty at PT Mitra Bisnis Keluarga, Cianjur Utara and North Sukabumi branches. The dependent variable used in this study is employee loyalty (Y). As for the independent variables (independent) used in this study are Profitability (X1), Work Environment (X2), and Employee Salaries (X3). The data used is quantitative data and is also primary data which refers to information obtained directly by researchers from direct sources, with sampling carried out by distributing questionnaires to respondents. The analysis test of this research uses the analysis of validity test, reliability test, multiple linear regression, and the coefficient of determination. Where before distributing to the original respondents, the questionnaire used in the validity and reliability tests first. After this test, the questionnaire was distributed to the original respondents. From the analysis of this study shows that the work environment (X2) has a significant effect on employee loyalty in a company.